MENGEMBANGKAN SOSIAL-EMOSIONAL MENGGUNAKAN PROJECT BASED LEARNING, DEMONSTRASI, MEDIA BARANG BEKAS (RO-TAN, GATEMPI) DI TK AISYIYAH BUSTANUL ATHFAL 37 BANJARMASIN - Diningsih, Lucky Prasetya; Purwanti, Ratna (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2025)
The problem in this study is the low results of social emotional development in group A children. This research approach uses a qualitative approach with the type of class action research, carried out in 4 meetings, the research setting in group A children totaling 13 children, 5 boys and 8 girls. Data collection techniques using observation, documentation and interviews as well as assessment of children's social emotional development aspects. This study aims to describe teacher activities, as well as analyze children's activities and aspects of social emotional development through a combination of Project Based Learning models, demonstration methods and used material media (RO-TAN and GATEMPI). The results showed that teacher activities increased with a very good category, children's activities increased by obtaining the BSB category and the achievement of social emotional development increased by getting the BSB category.